Antigen-Specificity in the Thymic Development and Peripheral Activity of CD4+FOXP3+ T Regulatory Cells - Pohar, Jelka; Simon, Quentin; Fillatreau, Simon (Frontiers in Immunology, 2018)
CD4+Foxp3+ T regulatory cells (Treg) are essential for the life of the organism. Remarkably, their role is not to defend the host against infectious diseases, but rather to protect it against the otherwise fatal intrinsically auto-aggressive nature of its own lymphocytes in particular of its own CD4+Foxp3- T conventional cells (Tconv). An essential challenge for this lymphocyte subset is therefore to suppress autoaggressive responses while allowing efficient host defence mechanisms against infectious diseases that would otherwise kill the host. This simple presentation of the general representation of Treg function underlines the central role that antigen-specificity must play in this mechanism of immune regulation. The role of antigen-specificity in Treg development, and in their activity in the periphery has however remained imprecisely understood due to the lack of knowledge of the antigens actually recognised by these cells during the different steps of their life. Recently, several studies provided novel knowledge on the endogenous antigens mediating the positive selection of autoreactive Treg in the thymus, underlining the extreme specificity of this process which appeared to be mediated by single autoantigens. Furthermore, several investigations quantitatively enumerated disease-relevant antigen-specific Treg and Tconv in autoimmune and allergic disorder. These studies also found that the protective function of Treg against immunopathology was highly specific, and that the development of immunopathology was permitted by a lack of Treg against the antigens targeted by the deleterious response rather than by a functional impairment of these cells. This review aims at presenting these novel data on the antigen-specificity of Treg development and function. The clarification of the antigen-specificity of Treg responses shall ultimately help at manipulating these cells therapeutically in autoimmune, malignant, and infectious diseases.